ANALYSIS OF DICTION AND LANGUAGE STYLE OF COMMERCIAL ADVERTISEMENT IN THE JAKARTA POST - Dicky Abdillah; Yunita Nugraheni; Budi Tri Santosa (Premise: Journal of English Education and Applied Linguistics, 2022)
This study aims to describe the diction and language style in the commercial advertisement of The Jakarta Post newspaper. This type of research is descriptive qualitative research. The data source used in this study is The Jakarta Post, published in October 2019. The data in this study are in the form of words, phrases, clauses, sentences, and expressions in the form of narrative that meet the classification of language style, diction, and advertisement style. Based on the analysis of 19 data, 11 data on Soft Style and 8 Hard Style advertisement styles were found, along with 13 data on connotation diction and 6 data on denotation diction. Meanwhile, 6 data on hyperbole language styles, five alliteration language styles, four metaphorical language styles, two personification language styles, and one each for assonance and metonym language style were found. In addition, the function of the language style is also found, namely 8 data functions to persuade the reader, 5 data functions to create a certain mood, 3 data functions to make the writer’s idea clearer, 2 data functions for the artistic effect of the idea being offered by the writer, and 1 data that serves to increase the reader’s taste. Interestingly, hyperbole is the favorite language style found in the 12 commercial advertisements in The Jakarta Post was published in October 2019, and its function is to persuade the readers.